Securing the world economy the reinvention of the League of Nations, 1920-1946 - Clavin, Patricia 1964- (Oxford University Press, 2013)
A study of the League of Nations' work in promoting economic and financial co-operation in the wake of the Great Depression, and a major account of the League's relationship with the USA in the 1930s and 1940s